Analisis Ketimpangan Distribusi Pendapatan di Indonesia Tahun 2015-2019 - Muhammad Daffa Rifaldo; Tri Wahyu Rejekiningsih (Diponegoro Journal of Economics, 2024)
This study aims to analyze the factors influencing why the Gini ratio, or income distribution inequality in Indonesia. The study employs a descriptive quantitative method, with parameter estimates obtained through panel data regression. The model is tested using the fixed effect model. The results show that the investment variables, represented by Domestic Investment (PMDN) and Regional Original Revenue (PAD), contribute to increasing income distribution inequality. The labor variable does not affect income inequality, while the individual internet usage (IPI) variable significantly reduces income inequality. The Human Development Index (HDI) variable does not affect income inequality, and the per capita GRDP, used as a dummy variable, also has no significant effect on income distribution inequality. The originality of this research lies in its use of technology variables, represented by Individual Internet Usage (IPI), and its background based on the National Medium-Term Development Plan (RPJMN) 2015-2019.